Effect of Hydrolytic Enzymes Production by Diazotrophs and Urea Fertilization on Root Colonization and Growth of Rice (Oryza Sativa L.) - Abdul Mutalib, Asilah (2010)
Production of hydrolytic enzyme by diazotrophs and their association with rice plant may increase the N2-fixing activity and subsequently plant growth. The ability to produce hydrolytic enzymes is an important mechanism of diazotrophs to enter the plant roots. Hydrolytic activities are important during colonization of the surface and interior of root by associative and endophytic diazotrophs. A series of experiments were conducted in laboratory and glasshouse conditions with the following objectives; (i) to screen for hydrolytic enzyme production in diazotrophs isolated from rice rhizosphere, (ii) to determine the effect of diazotrophs on hydrolytic enzyme activity, root colonization, root development and N2-fixing activity of rice, (iii) to determine the effect of urea-N on hydrolytic enzyme production, N uptake and growth of rice inoculated with diazotrophs. Twelve bacterial isolates were screened for the endoglucanase (EG) and endopolymethylgalacturonase (EPMG). The production of the hydrolytic enzymes, root colonization and root development of MR219 rice inoculated with selected diazotrophs (Sb34, Sb41 and Sb42) was determined in vitro. The effect of urea-N on production of these hydrolytic enzymes in rice inoculated with diazotrophs was evaluated under glasshouse condition. The inoculated (Sb42 strain) and non-inoculated plants were treated with three rates of urea-N (0, 30 and 60 kg/ha). Plants were harvested at 45 days after transplanting and analyzed for soluble protein content, specific enzymes activity, plant growth, concentration and uptake of N and photosynthetic activity. Results showed that nine out of 12 bacterial strains were positive with carboxymethyl cellulose (CMC) and pectin reactions as indicated by appearance of halo zone around the colonies. There was significant (P≤0.05) effect of different diazotrophic inoculation on the rice rhizosphere and endosphere populations. Populations of inoculated diazotrophs were found higher in the rhizosphere than the endosphere of rice. Inoculated plants showed significantly (P≤0.05) higher specific enzymes activity and soluble protein content compared to non-inoculated control. Inoculation significantly (P≤0.05) increased root growth of rice with substantial increases in root length, volume and surface area. Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) observations revealed the ability of diazotrophs to colonize the surface and interior of roots. Glasshouse study showed that growth of rice was significantly (P≤0.05) affected by diazotrophs and urea-N application. Low availability of nitrogen in soil stimulated the bacterial activity. Application of urea at 30 and 60 kg N negatively affected the interaction between diazotroph and rice plants. Inoculated plants without urea-N showed significantly (P≤0.05) higher specific hydrolytic enzymes activity, soluble protein content, plant biomass, photosynthesis activity and N uptake compared to other treatments. In general, diazotrophs produced substantial amount of hydrolytic enzyme which can improve nitrogen fixing activity in inoculated plants. Colonization of diazotrophs on the surface and interior of rice root is important for nitrogen fixation and plant growth enhancement. The association of these diazotrophs with the plants significantly (P≤0.05) increased the production of hydrolytic enzymes in the root system which is an important mechanism for endophytic colonization and subsequently nitrogen fixation.